Exploratory Data Analysis (EDA) pada Dataset Penjualan Video Game Global (1980-2020) - Adhitya Tisnadja (Journal of Smart Technology and Engineering, 2025)
The rapid development of the video game industry highlights the importance of analyzing sales data to understand global market preferences. This research applies the Exploratory Data Analysis (EDA) method to analyze a global video game sales dataset sourced from Kaggle. The objective is to identify factors influencing game sales success, such as platform, genre, publisher, and regional distribution. The EDA method involves data exploration, cleaning, visualization, and statistical analysis using Python and libraries such as Pandas, Matplotlib, and Seaborn. The analysis reveals that North America contributes the most to global video game sales, with the PlayStation 2 being the dominant platform. The most popular genres are Action, Sports, and Shooter. Furthermore, publishers like Nintendo and Electronic Arts are among the top contributors in terms of sales. This research provides valuable insights for game developers and publishers in designing effective and data-driven marketing strategies.